Zoonotic risks in urban areas: Prevalence of helminth parasites in urban populations of Lissachatina fulica in Sarawak, Malaysia - Farid Farhan, Mohd Nor; Nur Aniyah, Sulaiman; Tiffany Junior, Singgah Iddie; Dayang Norafizan, Awang Chee; Madinah, Adrus (British Veterinary Association (BVA) / Wiley, 2026)
Background: The giant African land snail (Lissachatina fulica), an invasive species with significant medical, agricultural and economic importance, is abundant in urban areas of Kota Samarahan, Sarawak. The proximity between humans and the snail may increase the risk of pathogen transmission. However, no study has examined the helminth prevalence in L. fulica from the area. This study aims to determine the prevalence of helminths in L. fulica collected from urban areas of Kota Samarahan, Sarawak. Methods: The mucus and faeces of the snails were analysed for helminths using direct microscopy, sodium chloride floatation, centrifugal sedimentation and Harada‒Mori filter paper culture. Results: As a result, 66 (44%) out of 150 individuals tested were positive for helminth infections. Sixteen helminth species were identified, comprising 13 nematode species, two cestode species and one trematode species. Conclusion and importance: The insights from this study will raise awareness of the negative impact of L. fulica on public health and the importance of controlling its population.